Violent Victimization in Emerging Adulthood and Its Longitudinal Impacts on Well-Being: A Study of Ever-Homeless Persons - Biro, Szilvia D. (Journal of interpersonal violence, 2025)
Persons who have experienced homelessness have higher lifetime risks of violent victimization relative to the general population. However, the long-term impacts of violent victimization on various facets of well-being are poorly understood among ever-homeless persons, particularly when violence is experienced in early adulthood. Here, using data from the National Longitudinal Study of Adolescent to Adult Health, we focus on a subsample of emerging adults who reported ever suffering homelessness (N = 481). Drawing primarily from Waves III and IV of the data, a series of regression models are specified to determine whether violent victimization in emerging adulthood is related to a range of negative outcomes later in life among ever-homeless persons (economic hardship, binge drinking, drug use, depression, offending, and victimization). Results indicate that victimization in emerging adulthood increases the risks for subsequent victimization for ever-homeless persons, but that it has no robust associations with any other outcomes examined. We explain these findings through processes of disadvantage saturation, in which the consequences of victimization may be more subdued among individuals who experience an array of hardships and disadvantages in their lives. The implications of these findings for policy are future research are discussed, and we emphasize the need for a context-contingent approach to the study of victimization and its life course consequences.